Händels Belshazzar - musikalische Form und geschichtliche Hintergründe - Assmann, Jan (Musik & Ästhetik, 2009)
Handel's "Belshazzar" ; Musical Form and Historical Background: Of all Handel's oratorios it is in Belshazzar (1744) that the music-theatrical character as opera and indeed "great opera" emerges most clearly in a new sense that went far beyond Italian opera seria. This is not only due to the form which is characterised by the choruses representing three different peoples (Jews Persians and Babylonians) but also the subject matter: the fall of Babylon and the liberation of the Jews from Babylonian imprisonment where worldhistorical and salvation-historical significance coincide. Through the combination of biblical and Greek sources Handel's librettist Charles Jennens showed the unique importance of the events in the year 539 BC here compressed into the space of a single day giving them a highly dramatic form and a near-mythical intensity that inspired Handel as he himself wrote to new ideas and means of expression